DPD and UGT1A1 deficiency in colorectal cancer patients receiving triplet chemotherapy with fluoropyrimidines, oxaliplatin and irinotecan. (22nd June 2015) - Falvella, Felicia Stefania; Cheli, Stefania; Martinetti, Antonia; Mazzali, Cristina; Iacovelli, Roberto; Maggi, Claudia; Gariboldi, Manuela; Pierotti, Marco Alessandro; Di Bartolomeo, Maria; Sottotetti, Elisa; Mennitto, Roberta; Bossi, Ilaria; et al.
<x xml:space="preserve">Abstract</x> Aims Triplet chemotherapy with fluoropyrimidines, oxaliplatin and irinotecan is a standard therapy for metastatic colorectal cancer (CRC). Single nucleotide polymorphisms (SNPs) in DPYD and UGT1A1 influence fluoropyrimdines and irinotecan adverse events (AEs). Low frequency DPYD variants (c.1905 + 1G > A, c.1679 T > G, c.2846A > T) are validated but more frequent ones (c.496A > G, c.1129‐5923C > G and c.1896 T > C) are not. rs895819 T > C polymorphism in hsa‐mir‐27a is associated with reduced DPD activity. In this study, we evaluated the clinical usefulness of a pharmacogenetic panel for patients receiving triplet combinations. Methods Germline DNA was available from 64 CRC patients enrolled between 2008 and 2013 in two phase II trials of capecitabine, oxaliplatin and irinotecan plus bevacizumab or cetuximab. SNPs were determined by Real‐Time PCR. We evaluated the functional variants in DPYD (rare: c.1905 + 1G > A, c.1679 T > G, c.2846A > T; most common: c.496A > G, c.1129‐5923C > G, c.1896 T > C), hsa‐mir‐27a (rs895819) and UGT1A1 (*28) genes to assess their association with grade 3–4 AEs. Results None of the patients carried rare DPYD variants. We found DPYD c.496A > G, c.1129‐5923C > G, c.1896 T > C in heterozygosity in 19%, 5% and 8%, respectively, homozygous rs895819 in hsa‐mir‐27a in 9% and homozygous UGT1A1*28 in 8%. Grade 3–4 AEs were observed in 36% patients and were associated with DPYD c.496A > G (odds ratio (OR) 4.93, 95% CI 1.29, 18.87; P = 0.021) and homozygous rs895819 in hsa‐mir‐27a (OR 11.11, 95% CI 1.21, 102.09; P = 0.020). Carriers of DPYD c.1896 T > C and homozygous UGT1A1*28 showed an OR of 8.42 (95% CI 0.88, 80.56; P = 0.052). Multivariate analysis confirmed an independent value for DPYD c.496A > G and c.1896 T > C. Conclusions Concomitant assessment of DPYD variants and the UGT1A1*28 allele is a promising strategy needing further validation for dose personalization.